Tool Building on the Shoulders of Others - Kienle, H.M.; Kuhn, A.; Mens, K.; van den Brand, M.; Wuyts, R. (IEEE software, 2009)
At the first International Workshop on Advanced Software Development Tools and Techniques, four emerging trends in academic tool building were evident. First, tools are increasingly constructed on the basis of external code, reusing, for instance, existing frameworks and integrated development environments. Second, researchers often choose dynamic languages such as Smalltalk to implement prototype tools. Third, Web-based tools are starting to incorporate Web 2.0 technologies to improve user interaction. Finally, increasing computational resources allow tools to tackle larger, real-world code bases.